DIGITAL STORYTELLING AND VOCABULARY DEVELOPMENT AMONG ENGLISH LEARNERS - Michael Anderson (International Journal of Literature and Language Studies, 2026)
This article explores whether digital storytelling supports vocabulary development among intermediate English learners. The study responds to the problem that vocabulary instruction is often separated from meaningful communication, although learners may remember words more effectively when lexical items are embedded in personal and multimodal narratives. Using mixed-method classroom inquiry combining descriptive score comparison with thematic analysis of learner reflections, the article analyzes student digital stories, vocabulary journals, and pre/post vocabulary tasks from an eight-week classroom project. The findings indicate that students showed improved productive use of target vocabulary and reported stronger emotional connection to new words when they used images, voice, and narrative sequencing. The article argues that digital storytelling can connect vocabulary learning with authorship, memory, and communicative purpose. By connecting language, literary form, and interpretation, the study offers a concise contribution to current debates in literature and language studies.